Effects of System Noise and Bribery on Collective Decision Rules. - Bodo, Peter (2008)
Developed and used Monte Carlo simulation models to test the effects of system moise and bribery on collective decision rules. He wrote simulation software, ran the simulations after debugging the software, analyzed the results and wrote a research paper, and presented the paper at the annual conference of the Eastern Economic Association. The paper will be published next year.
Keywords: dept.eco; faculty_collection; sabbatical_report

Economic liberalization and conditional volatility of exchange rate in sub-saharan africa: asymmetric GARCH analysis - Nandwa, Boaz; Andoh, Samuel K. (African Development Review-Revue Africaine De Developpement, 2008)
For small open economies, an understanding of movements in the exchange rate is imperative in analyzing trade and capital flows. In addition, reliable forecasting of exchange rate volatility is important in risk-taking assessment and investment decision-making, both of which are critical to long-term growth. Using an asymmetric GARCH-type approach, this paper examines the implications of economic liberalization on the stochastic behavior of the exchange rate series in a sample of sub-Sahara African (SSA) countries over the 1970-2004 period. The results indicate that exchange rate volatility is variable, and is less volatile under fixed exchange rate regime (pre-economic liberalization) and higher under flexible regime (post-economic liberalization), that is, it is asymmetric. For most of the countries, the EGARCH and TGARCH models are robust to parameter stability and gives better forecasting performance compared to the standard GARCH model.
2 citations (Crossref) [2023-10-31] tex.eissn: 1467-8268 tex.unique-id: ISI:000261215200004
Keywords: Africa; Sub-Saharan Africa; capital flow; decision making; dept.eco; exchange rate; forecasting method; investment; modeling; parameterization; stochasticity; trade flow; trade liberalization

Empirical relationship between macroeconomic volatility and stock returns: Evidence from Latin American markets - Abugri, Benjamin A (International Review of Financial Analysis, 2008)
Emerging market stock returns have been characterized as having higher volatility than returns in the more developed markets. But previous studies give little attention to the fundamentals driving the reported levels of volatility. This paper investigates whether dynamics in key macroeconomic indicators like exchange rates, interest rates, industrial production and money supply in four Latin American countries significantly explain market returns. The MSCI world index and the U.S. 3-month T-bill yield are also included to proxy the effects of global variables. Using a six-variable vector autoregressive (VAR) model, the study finds that the global factors are consistently significant in explaining returns in all the markets. The country variables are found to impact the markets at varying significance and magnitudes. These findings may have important implications for decision-making by investors and national policymakers. © 2006 Elsevier Inc. All rights reserved.
66 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/080-059-421-200-229 tex.type: [object Object]
Keywords: Emerging markets; Latin America; Macroeconomic volatility; Stock returns; Vector autoregressive model; dept.eco; dept.fin